Potencial da braquiária (Brachiaria decumbens Stapf) na fitorremediação de solos contaminados com arsênio - Antunes, Alessandra Silveira (2007)
Arsenic (As) has being considered since 1997 the top priority pollutant worldwide due to a variety of contamination sources. Environmental contamination of soils, waters, and sediments with As has also been detected close to industrial and mining areas in Brazil. Phytoremediation is an innovative, low-cost technique for these As-contaminated sites as it uses plants in the remediation of polluted soils with little soil disturbance. This study aimed at evaluating the As phytoextraction potential of Brachiaria decumbens growing under greenhouse conditions in six soils with contrasting texture and organic matter content: a Distrophic Yellow Latosol (LAd), a Distrophic Red Latosol (LVd), a Fluvic Neosol (RU), a Quartzenic Neosol (RQ), a Haplic Gleysol (GX), and a Melanic Gleysol (GM). Arsenic was added to soils as sodium arsenate (Na2HAsO4.7H2O) at rates of 0, 25, 50, 200, and 800 mg kg-1. The plants were collected 55 days after planting for determination of shoot and root dry matter production. Arsenic shoot and root contents were evaluated after digestion according to the USEPA 3051A method, following analysis by either flame or graphite furnace atomic absorption spectroscopy. A reduction in plant development was observed for rates greater than 50 mg kg-1 of As in the soils LAd, RQ, GX, and GM. For the soils RU and LVd such effects started only for rates greater than 200 mg kg-1. There was low translocation of As and consequently most of the As was detected in the roots. The low bioaccumulation factor of As by Brachiaria decumbens indicates that this species could be considered tolerant to the element but not an accumulator, thus being indicated for revegetation programs in As-polluted soils and sediments.